2010
DOI: 10.1177/000313481007600319
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Re-Excision in Patients with Early-Stage Breast Cancer Treated with Breast Conservation Therapy

Abstract: One of the risks of breast conservation surgery is local recurrence, which predominantly occurs as a result of inadequate surgical margins. The purpose of this study was to identify factors associated with close or positive surgical margins leading to reexcision (RE). The charts of 532 consecutive breast cancer patients treated at our center between September 2001 and June 2007 were reviewed to evaluate patients who opted for breast conservation surgery and needed reexcision. A total of 351 patients were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…The sensitivity advantage offered with MR imaging compared with conventional imaging increased with the increasing size of the DCIS component (from marginal to extensive to predominant DCIS types) and increased BREAST IMAGING: Invasive Breast Cancer with Ductal Carcinoma In Situ Component Kuhl et al cohort was very low (3.7%) and was independent of the presence or absence of a DCIS component. In comparison, the published positive margin rates observed after usual conventional assessment in similar cohorts range from 20.0% to 40.0% (1)(2)(3)(4)(5)(6)(7)29,30) and have been consistently reported to be higher in women with DCIS components than in those without DCIS components.…”
Section: Surgical Outcomementioning
confidence: 90%
See 1 more Smart Citation
“…The sensitivity advantage offered with MR imaging compared with conventional imaging increased with the increasing size of the DCIS component (from marginal to extensive to predominant DCIS types) and increased BREAST IMAGING: Invasive Breast Cancer with Ductal Carcinoma In Situ Component Kuhl et al cohort was very low (3.7%) and was independent of the presence or absence of a DCIS component. In comparison, the published positive margin rates observed after usual conventional assessment in similar cohorts range from 20.0% to 40.0% (1)(2)(3)(4)(5)(6)(7)29,30) and have been consistently reported to be higher in women with DCIS components than in those without DCIS components.…”
Section: Surgical Outcomementioning
confidence: 90%
“…Moreover, lesion localization and bracketing with guidewires is important to transfer the information regarding location and spatial extent of a biopsy-proved lesion into the presence of an intraductal (ductal carcinoma in situ [DCIS]) component as a major influencing factor; re-operation rates have been significantly higher for patients with versus those without DCIS components (1)(2)(3)(4)(5)(6). A survey of more than 55 000 women who underwent surgical treatment of breast cancer in England (6) confirmed that repeat surgery was nearly twice as likely when an invasive breast cancer had a DCIS component, with an average re-operation rate of 29.5%; re-operation rates of up to 87% have been reported for patients with larger (extensive) DCIS components (2). The survey (6) concluded that "lack of accurate imaging especially of DCIS components of invasive cancers is the main reason for positive margins and repetitive surgery."…”
Section: Breast Imaging: Invasive Breast Cancer With Ductal Carcinomamentioning
confidence: 99%
“…Recent reports from the literature concluding that ‘no ink on tumour equals adequate margin’ may test this possibility. Predictive factors (such as detection method, histological type, tumour size, nodal status and multifocal disease), preoperative strategies (such as axillary ultrasound and fine needle biopsy) and intraoperative strategies (such as frozen section, TIC or OSNA), may also reduce the need for re‐excision and ALND. The ability to predict either an incomplete excision or a positive SLNB, however, has limitations, and therefore, the cohort requiring re‐operation can only be accurately identified once the histopathology from the initial operative specimen is available.…”
Section: Discussionmentioning
confidence: 99%
“…At present, 18–50% of patients who undergo breast‐conserving therapy for breast cancer will have positive lumpectomy margins on final histopathology. These positive margins necessitate additional surgical procedures that cause patient stress and discomfort, worsen cosmetic outcomes and add to costs.…”
Section: Discussionmentioning
confidence: 99%
“…Achievement of microscopically clear margins is essential to minimize the risk of local recurrence after breast conservation . Unfortunately, attaining clear margins can be challenging, and rates of positive margins that require re‐excision range from 18 to 50% . In our institution, the re‐excision rate is 23.4% .…”
mentioning
confidence: 91%